The polymorphisms of beta-adrenergic receptors genes and a risk of atrial fibrillation development in patients with a heart failure - Pyvovar, Sergiy; Rudyk, Iurii; Lozyk, Tatyana; Galchinskaya, Valentina; Bondar, Tatiana (ScienceRise: Medical Science, 2019)
Objective: to study the relationship of gene polymorphisms of the b-adrenoreception system with the risk of atrial fibrillation in patients with heart failure. Material and methods. 286 patients with heart failure on the background of post-infarction cardiosclerosis were included. Of these, 25 (8.7 %) patients had the atrial fibrillation. The genotyping was performed using 4 polymorphisms (Gly389Arg of the b1-adrenoreceptors gene, Ser49Gly of the b1-adrenoreceptors gene, Gln27Glu of the b2-adrenoreceptors gene and Ser275 of the b3-subunit of G-protein gene) using the polymerase chain reaction. The genetic and epidemiological analysis was carried out using the SNPStats program. Results. Patients with heart failure with the G / C genotype of Gly389Arg polymorphism of the b1-adrenoreceptors gene have a lower risk of developing atrial fibrillation (OR=0.14 (0.03–0.61), p=0.0043, co-dominant model of heredity). The data on a decrease in the risk of atrial fibrillation in patients with heart failure and with the G/C genotype Gly389Arg polymorphism of the b1-adrenoreceptors gene are also confirmed in the overdominant (OR=0.15 (0.03–0.64), p=0.0012), as well as in the dominant (OR=0.23 (0.08-0.69), p=0.0029) and the log-additive (OR=0.40 (0.17-0.94), p=0.019) models. Findings. The results allow us to conclude that congenital genetic differences in the pathways of b-adrenoreception can be associated with the development of atrial fibrillation in patients with heart failure